Do the right thing: the imprinting of deonance at the upper echelons - Wesley, Curtis L. (Journal of business ethics, 2022)
This study expands the application of deonance theory into organizations’ upper echelons by examining how CEOs imprinted with a sense of duty can influence managerial decision-making. We hypothesize an imprint of bounded autonomy, an ought-force that constrains their decision-making and understanding of behavioral freedom, influences duty-bound CEOs to self-report errors in past financial reporting. We test deonance theory propositions of instrumentality for behavioral expansion, namely loss avoidance and gain attainment, related to institutional ownership concentration and CEO equity ownership. We use CEOs that are graduates of U.S. service academies as a proxy for duty-bound executives and find firms they lead are more likely to issue a financial restatement to correct a previous reporting error. This finding is robust to alternate explanations such as being error-prone, earnings management, auditor oversight, and risk behaviors. We also find evidence that deonance may be subject to behavioral expansion. The likelihood of issuing a restatement decreases as institutional ownership concentration and CEO equity ownership increases. This study shows imprinted deonance within the C-suite influences important organizational outcomes.